2010
DOI: 10.1177/1099636209359840
|View full text |Cite
|
Sign up to set email alerts
|

Static Performance of Hot Bonded and Cold Bonded Inserts in Honeycomb Panels

Abstract: An investigation on the structural performance of inserts within honeycomb sandwich panels is presented. The investigation considers metallic inserts in all aluminum sandwich panels and emphasis is placed on the structural performance difference between hot bonded and cold bonded inserts. The former are introduced during panel manufacture while the latter are potted into existing panels. The investigation focuses on the static performance of the two insert systems subject to loads in the normal direction to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(43 citation statements)
references
References 11 publications
0
37
0
Order By: Relevance
“…. Test parameters such as the insert diameter, insert depth, core thickness and core density and their effect on the pull-out resistance honeycomb-type sandwich mechanical joints [36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51]. These parameters are important to be followed in order to optimise the joint and to minimise failure caused by incorrect joint parameters.…”
Section: Pull-out Resistance Test Methods On Sandwich Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…. Test parameters such as the insert diameter, insert depth, core thickness and core density and their effect on the pull-out resistance honeycomb-type sandwich mechanical joints [36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51]. These parameters are important to be followed in order to optimise the joint and to minimise failure caused by incorrect joint parameters.…”
Section: Pull-out Resistance Test Methods On Sandwich Materialsmentioning
confidence: 99%
“…Failure load equations[36][37][38][40][41][42]50,51].Material EquationsHoneycomb sandwich-through-the-thickness insert FL = 0.29 × ML Honeycomb sandwich-fully potted insert FL = 0.86 × ML Honeycomb sandwich-partially potted insert FL = 0.99 × ML FL, Failure load (N); ML, Maximum load (N).…”
mentioning
confidence: 99%
“…In order to determine the reason behind the performance difference observed between the two insert systems a final element study was carried out [21]. The results from this study showed that the unexpectedly lower performance of the hot bonded inserts can be attributed to the stiffness of the filler material.…”
Section: Insert Pull-out Testsmentioning
confidence: 98%
“…There are a wide variety of different insert elements due to different and changing requirements and the absence of a uniform design approach. To give an example, in the manufacturing process, a distinction is made whether the insert is bonded during the production of the sandwich panel (hot bonded) or is installed after the production of the sandwich panel (cold bonded) (Bianchi et al 2010;Lim & Lee 2011). Other distinguishing criteria are the orientation of the connection, the decisive load case and the installation depth.…”
Section: State Of the Artmentioning
confidence: 99%